Distribuiç\~ao espacial de características sociodemográficas e localizaç\~ao de empregos e serviços públicos das vinte maiores cidades do Brasil - Rafael Henrique Moraes Pereira; Daniel Herszenhut; Carlos Kauê Vieira Braga; Jo\~ao Pedro Bazzo; Jo\~ao Lucas Albuquerque Oliveira; Jo\~ao Pedro Figueira Amorim Parga; Marcus Saraiva; Luiz Pedro Silva; Diego Bogado Tomasiello; Lucas Warwar (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
The development of several policies and research projects rely on data on the population socioeconomic characteristics and on the spatial distribution of economic activities and public services. Nonetheless, these data in Brazil are often difficult to access, require large computational power to process or come in different spatial resolutions. This study introduces the sociodemographic and landuse data set created in the Access to Opportunities Project, and describes in detail the methods used to create it. This data set consists in a hexagonal grid of high spatial resolution (area 0.11 km2) that aggregates information on the spatial distribution of the population (by age, sex, income and race), jobs and public services including schools (early childhood, primary and high school), public health services (low, medium and high complexity medical care) and referral centers for social assistance services. This edition of the data set covers the twenty largest cities in Brazil. The data is made publicly available by Ipea through the Access to Opportunities Project website and through the R package aopdata. We hope this work will help researchers and policy makers to more easily access high-quality data and use it in the decision-making processes involved in research and policy planning.
Keywords: J00; I00; R00; 330; population data; employment data; healthcare; schools; social assistance; public services; cities; Brazil